2022
DOI: 10.1186/s13567-022-01117-x
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma gallisepticum escapes the host immune response via gga-miR-365-3p/SOCS5/STATs axis

Abstract: A disruption in the expression of gga-miR-365-3p was confirmed in the Mycoplasma gallisepticum (MG)-infected Chicken primary alveolar type II epithelial (CP-II) cells based on previous sequencing results, but the role it plays in the infection was unclear. In the present study, we demonstrate that MG evaded cellular host immunity via a gga-miR-365-3p/SOCS5-JAK/STATs negative feedback loop. Specifically, we found that at the initial stage of MG infection in cells, gga-miR-365-3p was rapidly increased and activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Although inflammation is necessary to combat the spread of microbes, excessive inflammation can still cause tissue damage and is one of the key features of M. gallisepticum -induced CRD [ 70 ]. However, suppression of the innate immune response may have exacerbated M. gallisepticum infection [ 71 ]. This will be discussed in detail in the following section ( Section 5 ).…”
Section: The Innate Immune Response To M Gallisepticummentioning
confidence: 99%
See 2 more Smart Citations
“…Although inflammation is necessary to combat the spread of microbes, excessive inflammation can still cause tissue damage and is one of the key features of M. gallisepticum -induced CRD [ 70 ]. However, suppression of the innate immune response may have exacerbated M. gallisepticum infection [ 71 ]. This will be discussed in detail in the following section ( Section 5 ).…”
Section: The Innate Immune Response To M Gallisepticummentioning
confidence: 99%
“…The mRNA levels of IL-1β, IL-6, and CCL20, which are known to trigger an inflammatory response, peaked at 6 h following infection with M. gallisepticum in HD-11 cells and tracheal epithelial cells, then gradually decreased and reached the baseline 24 h post-infection [ 7 ]. Eight hours after M. gallisepticum infection in chicken primary alveolar type II epithelial cells, large amounts of TNF-α and IL-6 were produced and inflammation was suppressed 24 h after infection [ 71 ]. M. gallisepticum causes a strong inflammatory response but does not stimulate certain classical cytokines and it has been shown to transiently activate and then inhibit the inflammatory response [ 75 ], which may be one of the reasons for immune dysregulation and evasion of premature clearance by the organism.…”
Section: Escape From Innate Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…There is a summary of twenty recent studies that have addressed metastasis with medicines that interfere with communication mediators in signalling pathways, as shown in Table 3. For instance, twelve studies interfered with communication mediators using inhibitors, including AXL receptor tyrosine kinase (AXL) [117][118], miR-135a-5p [119][120], messenger RNA (mRNA) B-cell lymphoma-6 (BCL6) [121][122], TGFβ1 [123][124], T-cell immunoglobulin and mucin-domain containing protein-3 (Tim-3) [125] [126], and suppressor of cytokine signalling-5 (SOCS5) [127] [128]. These inhibitors interfered with miR-29a-3p, BMSC-derived exosomal lymphocyte cytosolic protein-1 (LCP1), miR-101 EV, CRISPR-associated protein-9 (Cas9), M2 mediation, and signal transducers and activators of transcription (STAT)-1 mediation by suppressing long intergenic non-protein coding RNA (linc)-00852 in the jumonji and AT-rich interaction domain containing 2 (JARID2) axis; neuregulin receptor degradation protein-1 (NRDP1) in the Janus kinase-2 (JAK2)/STAT3 signalling pathway; ADMSC-derived miR-101; CAF and α-smooth muscle actin expression and fibronectin (ASMAFN) differentiation; IL-10, TGFβ, and vascular endothelial growth factor (VEGF) secretions; and collagen type VI alpha 1 (COL6A1) from histone3 lysine27 acetylation (H3K27ac) activated in CAF conversion with IL-6 and IL-8 secretions; respectively.…”
Section: Interfere Communication Mediators' Therapiesmentioning
confidence: 99%
“…The MG-HS strain, a virulent strain, was isolated from Hubei, and pMGA1.2 is a major adhesion protein of MG-HS and is necessary for MG-HS infection in chickens [ 6 ]. Worse, our previous studies have demonstrated the ability of MG to evade host immunity through the gga-mir-365-3p/SOCS5/STATs axis [ 7 ]. Elimination of the risk of MG infection is a challenge for the poultry industry [ 8 ].…”
Section: Introductionmentioning
confidence: 99%